Aplicação do HFSS para análise do efeito de vértices no patch de antenas de microfita: compilado de artigos publicados em 2024 - PINTO, Samantha Mota (2024)
In this work, papers entitled “Analysis of the effects caused by the increase of vertices on the regular patch of a microstrip antenna” and “Analysis of the effects of a regular polygonal slot on a circular patch microstrip antenna”, developed during the period from 09/04/2023 to 08/31/2024, through the execution of the Undergraduate Research Project (PIBIC) PRO6432-2023, under the guidance of Prof. Dr. André Felipe Souza da Cruz, are presented. The first paper describes a microstrip antenna project in the High-Frequency Structure Simulator (HFSS), with a square patch fed by a 50 Ω coaxial cable beneath the ground plane, operating at a frequency of 2.59 GHz. From this design, simulations were conducted for two sets of antennas, varying the geometry of the patch into regular polygonal shapes, where return loss (S11), Voltage Standing Wave Ratio (VSWR), input impedance Z, and bandwidth (BW) were evaluated. The second paper focused on an analysis of the effects produced by a regular polygonal slot when inserted into the patch of a circular antenna with a radius of 1.69 cm, designed to operate at 2.4 GHz and coaxial cable feed at 30% from the center, also designed using HFSS. For this design, simulations were performed varying the relative position θ from 0◦ to 90◦ of the slot and the number of sides N from 4 to 12. It was found that the case of the antenna with a heptagonal slot produced the largest bandwidth, and for this case, the proportionality factor K was varied to observe the effects of the slot area on the antenna response. The same performance parameters as in the first paper were evaluated in the second paper. Both papers are available as an appendix and are connected by an integrative introductory text.